Comprehensive and Durable Modulation of Growth, Development, Lifespan and Fecundity in Anopheles stephensi Following Larval Treatment With the Stress Signaling Molecule and Novel Antimalarial Abscisic Acid - Taylor, Dean M.; Olds, Cassandra L.; Haney, Reagan S.; Torrevillas, Brandi K.; Luckhart, Shirley (Frontiers in Microbiology, 2020)
The larval environment of holometabolous insects determines many adult life history traits including, but not limited to, rate and success of development and adult lifespan and fecundity. The ancient stress signaling hormone abscisic acid (ABA), released by plants inundated with water and by leaf and root fragments in water, is likely ubiquitous in the mosquito larval environment and is well known for its wide ranging effects on invertebrate biology. Accordingly, ABA is a relevant stimulus and signal for mosquito development. In our studies, the addition of ABA at biologically relevant levels to larval rearing containers accelerated the time to pupation and increased death of A. stephensi pupae. We could not attribute these effects, however, to ABA-dependent changes in JH biosynthesis-associated gene expression, 20E titers or transcript patterns of insulin-like peptide genes. Adult females derived from ABA-treated larvae had reduced total protein content and significantly reduced post blood meal transcript expression of vitellogenin, effects that were consistent with variably reduced egg clutch sizes and oviposition success from the first through the third gonotrophic cycles. Adult female A. stephensi derived from ABA-treated larvae also exhibited reduced lifespans relative to controls. Collectively, these effects of ABA on A. stephensi life history traits are robust, durable and predictive of multiple impacts on an important malaria vector spreading to new malaria endemic regions.